Florida Carpon Desmodium - Martin B. Adjei; Albert E. Kretschmer, Jr. (EDIS)
Florida carpon desmodium (Figure 1), Desmodium heterocarpon, is among the few perennial summer-growing, grazing-tolerant, herbaceous pasture legumes available to Florida cattle producers. This document is SS-AGR-112, one of a series of the Agronomy Department, UF/IFAS Extension. Original EDIS publication date February 2006.